Dėl žem. jeĩnis - Zinkevičius, Zigmas (Baltistica, 1972)
CONCERNING SAMOGITIAN jeĩnis The pronoun jeĩnis, -ė ʽhe, she’, noticed by V. Grinaveckis in a Samogitian dialect of Lithuanian, is treated as an emphatic pronoun by the author of this paper. The pronoun originated on the basis of the epenthetic forms Acc. Sg. fem. jeĩnę and Instr. Sg. fem. jéine, used side by side with the regular dialect jeñję, jénje (= Standard Lith. Ją̃ją, ją́ja). The Nom. Sg. fem. jeĩnė (next to jeĩnę : jéine) appeared according to the pattern kárvė : karvę : kárve; the Nom. Sg. masc. jeĩnis arose (next to jeĩnė) according to the pattern medìnis : medìnė.